The Strategic Demand for Children: Theory and Implications for Fertility and Migration - B. Douglas Bernheim; Oded Stark (Harvard University, Center for Population Studies, 1986)
Intra-familial conflict which arises from individual consumption choices in an environment characterized by mutual altruism and direct consumption externalities results in parents receiving from their children less than the desired level of attention. Parents adopt a joint bequest-fertility strategy in order to extract from their children the desired level of attention, producing that number of children which, in conjunction with such a manipulative behavior, results in optimal extraction. Fertility implications are drawn, especially under alternative assumptions about the mortality regime. Predictions of the theory for investment in children's human capital and migration are delineated.
Keywords: 330